SUNTINGAN NASKAH MURWAKALA - Masitoh, Siti (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Murwakala is the story of the puppet show that is usually used in the Javanesse traditional seremonial namely ruwatan. Since it is oral tradition, it should be changed into the written text when it is analyzed further through the phylological process. The main process in philological activities is determining the most reliable text form. For this purpose, it is necessary to understand particular knowledge on the author, culture and tradition that have influence on the work. This is due to the fact that the main task of philology is criticism towards text and the purpose of the text criticism is the text that is the closest version to the original text. It should be done because usually every story teller has his own style in telling the story, that leads to the variations. In order to get the story which has the best quality, the textual comparation should be done. This article presents those process to get the best written text.Keywords: Murwakala, Filologi, Ruwatan